Association between recurrence risk perception and health behavior in patients with recurrent ischemic stroke in China: the mediation effect of self-efficacy - Zhang, Huan; Wu, Yao; Pu, Jiangfeng; Yuan, Lifang; Tian, Xingyin; Li, Yingying (Frontiers in Psychology, 2025)
BackgroundThis study aims to explore the relationship between recurrence risk perception and health behavior in patients with recurrent ischemic stroke, and the mediating effect of self-efficacy between recurrence risk perception and health behavior.MethodThis cross-sectional study was conducted from May 2023 to November 2023 in China on 280 recurrent ischemic stroke patients. Data on sociodemographic and clinical characteristics, the Recurrence Risk Perception Scale for Stroke Patients (RRPS-SP), the General Self-Efficacy Scale (GSES), and the Health behavior Scale of Stroke Patient (HBS-SP) were included in this study.ResultThere were 266 valid questionnaires (95% effective recovery rate). In correlation analysis, high recurrence risk perception and high self-efficacy were significantly associated with better levels of health behavior (P < 0.05). In the multiple linear regression model, after controlling for sociodemographic variables and clinical characteristics information in the t/F test (P < 0.05), it was found that recurrence risk perception and self-efficacy were significant predictors of health behavior, and that exercise status, Course of Disease, and family history of stroke in the sociodemographic and clinical characteristics information in the present study had a significant effect on health behavior (P < 0.05). Self-efficacy partially mediated the relationship between recurrence risk perception and health behavior (95% CI 0.102 to 0.334), with the mediating effect accounting for 37.3% (0.202/0.541)of the total effect.ConclusionRecurrence risk perception and self-efficacy were influential factors in promoting health behavior. In addition, the effect of recurrence risk perception on health behavior was mediated by self-efficacy.